Analysis of Government Expenditure Response, Foreign Direct Investment, Human Development Index and Inclusive Economic Growth in Indonesia - Ilmi Marina; Alpon Satrianto (Jurnal Ekonomi Pembangunan, 2023)
This study aims to analyze the response to shocks that occur between the variables Government Expenditure, Foreign Investment, Human Development Index, and Inclusive Economic Growth. This type of research is descriptive and inductive. The data used are panel data for 34 provinces in Indonesia from 2012-2020, data obtained from related agencies. The analysis method used is the Panel Vector Error Correction Model (PVECM). The results of this study show that: (1) The response to government expenditure in the education function due to the shock of inclusive economic growth is positive, (2) The response to government expenditure in the health function due to the shock of inclusive economic growth is positive (3) The response to government expenditure in the economic function due to the shock of inclusive economic growth is negative (4) The response of foreign investment due to the shock of inclusive economic growth is negative (5) The response of the human development index due to the presence of  Shock of Inclusive Economic Growth Is Positive.